Asset Pricing, Investment, and Trading Strategies - Wong, Wing-Keung (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Asset pricing, investment, and trading strategies are very important in finance. They are useful in various situations, for example, supporting the decision-making process of choosing investments; determining the asset-specific required rate of return on the investment; pricing derivatives for trading or hedging; getting portfolios from fixed incomes or bonds, stocks, and other assets; evaluating diverse portfolios; determining macroeconomic variables affecting market prices; calculating option prices; and incorporating features such as mean reversion and volatility, etc. They can also be applied in financial forecast for assets, portfolios, business projects.Understanding, modeling, and using various asset pricing models, investment models, and models for different trading strategies is paramount in many different areas of finance and investment, including banking, stocks, bonds, currencies, and related financial derivatives. Different asset pricing models, investment models, and models for different trading strategies also allow us to compare the performances of different variables through the analysis of empirical real-world data.This Special Issue on "Asset Pricing, Investment, and Trading Strategies" will be devoted to advancements in the theoretical development of various asset pricing models, investment models, and models for different trading strategies as well as to their applications.The Special Issue will encompass innovative theoretical developments, challenging and exciting practical applications, and interesting case studies in the development and analysis of various asset pricing models, investment models, and models for different trading strategies in finance and cognate disciplines.